System for Women's Security using IoT - T. Sunitha, B. Rama Devi, A. Swathi, D. Ashok, B. Mouli Chandra (Mathematical Statistician and Engineering Applications, 2023)
All young women, women of all walks of life, and individuals struggle daily to protect themselves from the wandering eyes of highly ill-mannered men who abuse young women's attitudes. The Blade IoT implementation includes Raspberry Pi, temperature and heart-rate sensors, Global PS, panic pin, and camera all included. This tiny device uses a Raspberry Pi camera to take pictures of the attacker and instantly transfer the bleeding victim's rim area when the victim's pulse. It can be activated by the victim by hitting a button. A legal authority or predetermined contact information can get the position and connection of the taken image and SMS. We also use voice factor, a technique a woman uses to when she pushes the button to ask for help when she is not in a crisis, a message is sent to the